Changes of beneficiaries after Red Cross safe motherhood project in Northern Uganda - Ai, Ogata; Mie, Naiki; Yukiya, Saito; Onzima, Alex (African Journals Online (AJOL), 2024)
Background: The Japanese Red Cross Society (JRCS) and the Uganda Red Cross Society (URCS) collaboratively implemented the safe motherhood project for women of reproductive age and community people to improve reproductive health in Northern Uganda from 2010 to 2016. Follow-up visit has not been conducted and the information on detailed changes of the beneficiaries were limited. Objectives: To explore the beneficiaries’ changes after the Red Cross safe motherhood project in Northern Uganda. Methods: Study design was qualitative content analysis using interview guides. Findings: After the approval of Institutional Review Board Clearance, the study was started. All participants of the study were informed the study objectives, methods, and ethical considerations and consented to participate. The study participants were six people, three beneficiary couples. Changes in knowledge of safe motherhood and general healthcare, attitude helped and prepared financially, attitude to look women as valuable people, practice of visiting health center to get something, practice of avoiding infectious diseases, practice of increment of ANC visit and facility-based delivery, practice of male involvement for safe motherhood were derived from the interview. Conclusion: Follow-up visit revealed positive changes of beneficiaries after the project, however continuous support is needed for sustainability of the safe motherhood project. Keywords: Beneficiaries; Red Cross safe motherhood; Northern Uganda.